Cooperatives in the agri-food environment from a private law perspective - Marín Cáceres, Laura (Przegląd Prawa Rolnego, 2021)
Organisations made up of individuals who join together to achieve a common goal by taking joint action are a preferred form of activity in the agricultural sector and refers to cooperative societies and the advantages they provide from the point of view of the individual small grower or breeder. The general legal regime of cooperatives was established in Spain by Act 27/1999 of 16 July 1999, but there are also a number of autonomous regulations that also govern this sector. The considerations presented in the article, thanks to the analysis of important practical aspects such as the observance of the guiding principles, as well as the structure and operation of cooperatives, show their practical importance in the agricultural sector in Spain.